Income Smoothing due to Unemployment Concerns - NG, Jeffrey (Institutional Knowledge at Singapore Management University, 2015)
Economic theory predicts that top executives and lower-level employees have incentives to smooth income due to compensating wage differential costs and fear of job loss, respectively. Following Agrawal and Matsa (JFE, 2013) who rely on exogenous variations in unemployment insurance benefits to examine how unemployment concerns affect corporate leverage, we examine the link between such benefits and income smoothing. We find that when unemployment insurance benefits are higher and concerns about unemployment are hence lower, there is less income smoothing. This relation is stronger when employees face higher unemployment risk and weaker when the firms’ information and internal control environments are strong. Our study contributes to the literature by showing that labor market policies have a significant, likely unintended externality on corporate financial reporting.